ANALISIS KREDIBILITAS SOCIAL MEDIA INFLUENCER DI INSTAGRAM PADA PERILAKU PEMBELIAN GENERASI Z - Vaneza Vaniaruby Setiyanto, (2021)
Credibility is important thing and must be owned by a social media influencer. In addition to releasing information that affects their communicants, they must also have credibility that is valued and viewed only by their communicants. Nowadays, many social media influencers are promoting a product / service through their Instagram account. In this study, it will be linked to generation Z, they are the generation born in 1996-2010. This generation is the internet generation because it was born and raised in an all-digital era accompanied by advanced technology that affects their personality and behavior. They are certainly also aware of the existence of social media influencers. Their buying behavior is also influenced by promotions from social media influencers. This research uses descriptive qualitative method. The data source used is from interviews, as well as the documentation collected. The theoretical basis used is the source credibility theory. The result of this research is that Fadil Jaidi is considered a credible source by Generation Z and fulfills the credibility aspects of the source, namely trust, expertise, attractiveness, and equality. Their buying behavior is also influenced by these aspects and raises brand awareness. Keywords: Credibility, social media influencer, Z generation, buying behavior